Phase I study of alvocidib plus cytarabine/mitoxantrone or cytarabine/daunorubicin for acute myeloid leukemia in Japan. Issue 12 (10th October 2022) - Ikezoe, Takayuki; Ando, Kiyoshi; Onozawa, Masahiro; Yamane, Takahisa; Hosono, Naoko; Morita, Yasuyoshi; Kiguchi, Toru; Iwasaki, Hiromi; Miyamoto, Toshihiro; Matsubara, Keisuke; Sugimoto, Saori; Miyazaki, Yasushi; et al.
Abstract: Therapeutic improvements are needed for patients with acute myeloid leukemia (AML), particularly those who have relapsed or who have treatment‐refractory (R/R) AML or newly diagnosed patients with poor prognostic factors. Alvocidib (DSP‐2033), a potent cyclin‐dependent kinase 9 inhibitor, has previously demonstrated promising clinical activity for the treatment of AML. In this multicenter, open‐label, uncontrolled, 3 + 3 phase I study, we investigated the safety and tolerability of alvocidib administered in combination with either cytarabine and mitoxantrone (ACM) for R/R AML or cytarabine/daunorubicin (A + 7 + 3) for newly diagnosed AML. Alvocidib was administered to all patients as a 30‐min intravenous (i.v.) bolus (30 mg/m 2 /d), followed by a continuous i.v. infusion over 4 h on days 1–3 (60 mg/m 2 /d). A total of 10 patients were enrolled: six received ACM (at two dose levels of cytarabine and mitoxantrone) and four received A + 7 + 3. Alvocidib was tolerated and no dose‐limiting toxicities were observed. All patients experienced adverse events, of which diarrhea was the most frequent (100%); hematologic events were also common. Alvocidib concentration peaked at the end of dosing (4.5 h after start of administration), plasma accumulation after repeated dosing was minimal and urinary excretion was negligible. The rate of complete remission/complete remission with incomplete hematologic recovery was 66.7% with the ACM regimen in R/R AML, including four complete remission (median duration 13.6 months), and 75% (three complete remission) with the A + 7 + 3 regimen. Further development of alvocidib in hematologic malignancies is warranted. The trial is registered with Clinicaltrials.gov, NCT03563560. Abstract : The data demonstrated that both alvocidib regimens had an acceptable safety profile in Japanese patients with AML. The clinical activity was also promising, although this was a very small group of patients.